(untitled) (Confluenţe Bibliologice, 2025)
The article renders about the most important events in the life and work of Sámuel Teleki, a Romanian lover of books, who was the founder of Teleki library-the most valuable cultural institution in the city of Tîrgu-Mureş. His contributions are mentioned: the library catalogue, processing and thematic structure of the fund. Collection of Samuel Teleki and the Bolyai collection includes encyclopedias, philosophical works, Greek literature, Latin and bibliophile rarities.